Role of exosomal microRNAs in cancer therapy and drug resistance mechanisms: focus on hepatocellular carcinoma - Zelli, Veronica; Compagnoni, Chiara; Capelli, Roberta; Corrente, Alessandra; Di Vito Nolfi, Mauro; Zazzeroni, Francesca; Alesse, Edoardo; Tessitore, Alessandra (Frontiers in Oncology, 2022)
Extracellular vesicles (EVs), defined as intercellular messengers that carry their cargos between cells, are involved in several physiological and pathological processes. These small membranous vesicles are released by most cells and contain biological molecules, including nucleic acids, proteins and lipids, which can modulate signaling pathways of nearby or distant recipient cells. Exosomes, one the most characterized classes of EVs, include, among others, microRNAs (miRNAs), small non-coding RNAs able to regulate the expression of several genes at post-transcriptional level. In cancer, exosomal miRNAs have been shown to influence tumor behaviour and reshape tumor microenvironment. Furthermore, their possible involvement in drug resistance mechanisms has become evident in recent years. Hepatocellular carcinoma (HCC) is the major type of liver cancer, accounting for 75-85% of all liver tumors. Although the improvement in HCC treatment approaches, low therapeutic efficacy in patients with intermediate-advanced HCC is mainly related to the development of tumor metastases, high risk of recurrence and drug resistance. Exosomes have been shown to be involved in pathogenesis and progression of HCC, as well as in drug resistance, by regulating processes such as cell proliferation, epithelial-mesenchymal transition and immune response. Herein, we summarize the current knowledge about the involvement of exosomal miRNAs in HCC therapy, highlighting their role as modulators of therapeutic response, particularly chemotherapy and immunotherapy, as well as possible therapeutic tools.